Factors which may be preventing the recovery of populations of helmeted guineafowl in the midlands of KwaZulu-Natal - Ratcliffe, Charles Stansfield (University of Cape Town, 2014)
Bibliography : leaves 134-152. === The Helmeted Guineafowl Numida meleagris is, naturally, a species of open savannas. However, since the mid-18th century, it has undergone the most extensive range expansion of any African gamebird. In southern Africa, this expansion has been mostly due to a combination of deliberate introductions and the natural expansion into areas transformed by agriculture and urban development, which supply key resources such as food, cover, roosting sites and watering points. The Midlands of KwaZulu-Natal province have been no exception in this regard. With the advent of, in particular, crop agriculture, large populations of guineafowl have occupied, and increased numerically in, this variegated landscape since the turn of the 20th century .